“Jogo Tonggo” Efektivitas Kearifan Lokal; Solusi Pandemi Covid-19 - Muh Fajar Shodiq (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
The Covid-19 pandemic has entered its 2nd year. This epidemic hit all aspects of people's lives, from the aspects of health, education, tourism, economy, social, culture, politics to 'changing' civilization. Various ways have been taken by various parties to be able to remain healthy and still be able to "live" in the midst of a pandemic that no one can be sure of when it will end. “Jogo tonggo” is one of the local wisdom-based programs launched by the Governor of Central Java, Ganjar Pranowo, which is predicted to be able to overcome various sectors, especially the economy, health and social sectors. This local wisdom of jogo tonggo has proven to be effective in helping food security, accelerating the rate of information regarding the handling and education of Covid-19, triggering human moral awareness to comply with regulations and create solidarity to protect each other and meet the needs of neighbors so as to increase the immunity of Covid-19 sufferers (OTG) and their families until the cure rate for Covid-19 patients can increase.Keywords: Jogo Tonggo; Effectiveness; Local Wisdom; Covid 19 AbstrakPandemi Covid-19 sudah memasuki awal tahun ke-2. Wabah ini memukul seluruh sendi kehidupan masyarakat, mulai segi kesehatan, pendidikan, pariwisata, ekonomi, sosial, budaya, politik sampai ‘mengubah’ peradaban. Berbagai cara ditempuh oleh berbagai pihak untuk bisa tetap eksis sehat dan tetap bisa ‘hidup’ ditengah pandemi yang tidak ada yang bisa pastikan kapan berakhir. ‘Jogo tonggo’ adalah salah satu program berbasis kearifan lokal yang dicanangkan oleh Gubernur Jawa Tengah, Ganjar Pranowo yang digadang-gadang mampu mengatasi berbagai sektor terutama ekonomi, kesehatan dan sosial. Kearifan lokal jogo tonggo ini terbukti efektif membantu ketahanan pangan, percepat laju informasi mengenai penanganan dan edukasi mengenai covid-19, memicu kesadaran moral kemanusiaan untuk taati peraturan serta timbulkan solidaritas saling menjaga dan pemenuhan kebutuhan tetangga hingga bisa meningkatkan imunitas penderita Covid-19 (maupun OTG) dan keluarganya hingga tingkat kesembuhan pasien Covid-19 bisa meningkat.Kata Kunci: Jogo Tonggo; Efektifitas; Kearifan Lokal; Covid 19